2006
DOI: 10.1590/s1677-54492006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Implante de filtro de veia cava inferior guiado por ultra-som: relato de dois casos

Abstract: The percutaneous placement of inferior vena cava filters is traditionally carried out in angiosuite or operating room using fluoroscopy and infusion of iodinated contrast for proper positioning of the device. However, for patients hospitalized in intensive care units under poor conditions for transportation, and for patients with impaired renal function, their displacement and the nephrotoxicity of the iodinated contrast agents are frequently matters of concern. Thus, the bedside placement of inferior vena cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some authors have also described filter placement using ultrasound control when there is a duplicated vena cava. [6][7][8] There are few reports of filter placement in the vena cava in this situation. We report a case of vena cava filter placement in suprarenal position in a patient with duplicated IVC.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also described filter placement using ultrasound control when there is a duplicated vena cava. [6][7][8] There are few reports of filter placement in the vena cava in this situation. We report a case of vena cava filter placement in suprarenal position in a patient with duplicated IVC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it is feasible to implant vena cava filters with guidance by abdominal ultrasonography, particularly for high-risk patients or those with significant renal dysfunction. 5,17,18 The objective of this study was to identify simple parameters that could serve, in the majority of cases, as an aid to anatomical assessment to guide safe release of vena cava filters. Considering that the vertebral bodies can be seen during radioscopy, correlations between the anatomic positions of the renal veins and these structures could be used as a guide to the ideal site for release.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have advocated preventative (in the absence of proven deep venous thrombosis or pulmonary embolism) implantation of a vena cava filter after a trauma, on the basis that it reduces the incidence of severe thromboembolic events in these cases and because it involves temporary interruption of the vena cava [9][10][11][12] . The majority of filters are fitted with the aid of fluoroscopy, using iodine-based contrasts in specific sectors, but for patients at high risk from transportation, they can be fitted at the bedside with the aid of vascular Doppler ultrasound 13 . The rate of removal of retrievable filters is still low, which can be attributed to the clinical conditions of multiple trauma patients and to failures by the services that implant filters to follow-up their patients afterwards 14 .…”
Section: Discussionmentioning
confidence: 99%